Mitigation of vibrations and re-radiated noise in buildings generated by railway traffic: a parametric study - Colaço, Aires (2017)
In the last decades, the number of railway projects in urban environment has continuously increased. This rising requires a significant level of knowledge from the scientific and technical communities about the phenomena of generation and propagation of vibrations with emphasis on its interference in nearby buildings and the consequent nuisance of their occupants. In this context, a numerical model to predict vibrations and re-radiated noise in buildings induced by railway traffic is presented. The model is based in a sub-structuring approach, where the whole propagation media is considered, from the vibration source (vehicle-track interaction) to the receiver (building and interior acoustic media). The track-ground-building system is simulated by a 2.5D FEM-PML model, formulated in the frequency - wavenumber domain. The re-radiated noise evaluation is based on a 2.5D FEM-MFS model, where the FEM is used to obtain the structural response. The computed structural displacements are then used as vibration input to the Method of Fundamental Solutions (MFS) model in order to assess the acoustic response in the building's enclosures. Finally, a parametric-study focused in the evaluation of the influence of a mitigation measure in the reduction of the vibrations and re-radiated noise levels is presented.